Effects of Fertilization on Stoichiometric Characteristics, Rhizosphere Microorganisms and Metabolites Under Substrate Cultivation for Pepper - Qianqian Di; Enling Ji; Qingjie Du; Guilan Gu; Juanqi Li; Meng Li; Hu Wang; Panqiao Wang; Huaijuan Xiao (Horticulturae, 2025)
Substrate cultivation is a widely used method in greenhouses to address the deterioration of the soil environment caused by excessive fertilization. However, the effects and relationships of fertilization treatments on stoichiometric characteristics, rhizosphere soil microorganisms, and metabolites are still unclear. To determine the optimal amount and frequency, two fertilization intervals (every 5 days and every 10 days) and four total fertilization levels (378.5, 529.9, 605.6, and 757.0 kg·ha−1) were considered, along with a control (CK). Among the treatments, T6 (every 10 days with a total fertilization amount of 605.6 kg·ha−1) resulted in the best pepper plant growth, highest photosynthetic capacity, and maximum yield. Fertilization significantly changed the species composition and community structure of rhizosphere microorganisms. It also affected the composition of rhizosphere metabolites, with differential metabolites significantly enriched in alanine, aspartate, and glutamate metabolism, as well as butanoate metabolism. This study provides insights into high-quality and high-yield cultivation of peppers, as well as the rhizosphere microorganisms and metabolites that play an important role in production.